How Starbucks Maintain Its Competitive Edge? – The Secret of Its Success - Daisy Mui Hung Kee; Nor Hidayah; Hayatun Syamilah; Nik Nooratikah Nasuhah; Noor Husnina Syasya; Wan Norathirah (AIBPM Publisher, 2021)
This research paper aims to investigate the secrets of how Starbucks maintains its progress to ensure the success of its brand competitive edge. The findings highlight that Starbucks focuses on selling coffee beans and utilizing high-quality equipment that helped it manage to impress the customers with its sophisticated coffee making, including a wide variety of attractive and delicious beverage menus. Starbucks puts much innovation and creativity until it thrives in the global coffee industry, presenting challenges related to ethics and responsibilities within many aspects due to its system theory. Starbucks gained worldwide market demand, and successfully remains a leading brand in the coffee industry with a globalization design from an international broader context.